Análise da estrutura populacional de Aedes aegytpi (Linnaeus, 1762) em algumas regiões do Brasil - Bronzato, Aline Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Aedes aegypti is considered the main vector of arboviruses affecting humans. Nowadays, the only feasible measure to eradicate the dengue fever depends exclusively of vector control. The deep knowledge about the structure and dynamics of Ae. aegypti population in distinct environments is critical, since genetically different populations may present differences related to vector competence and capacity. Brazil has regions with different climatic and geographic characteristics, therefore, detailed knowledge about mosquito population that colonizes different habitats is extremely important. The present study evaluated the population structure of Ae. aegypti mosquitoes in five different Brazilian cities (i.e., Belo Horizonte, Botucatu, Campo Grande, Maringá and Rondonópolis) using a microsatellite markers. Those markers were also used to evaluate the oviposition dynamic and the consequences of Ae. aegypti mosquitoes dispersion, of the city of Botucatu. Population macro-analysis, using DAPC evidenced, genetic clusters among individuals of the same locality, and population structure in mosquitoes of Belo Horizonte. Population microstructure analysis identified six sub-populations of Ae. aegypti mosquitoes among six sub-regions of Belo Horizonte. In addition, the microstructure analysis suggested intermediate population structure in the sub-regions of Campo Grande, and lack of genetic structure among mosquitoes from the sub-regions of Botucatu. Therefore, these results indicate that genetic organization occurs in correlation with city size - where large towns seem to provide genetic structure to the populations of Ae. aegypti. PCA analysis of ovitraps obtained in Botucatu indicated population organization of Ae. aegypti mosquitoes in families. Pedigree analysis and inbreeding coefficient indicated that only for out of 30 mosquitoes analyzed in the same ovitrap, keep restricted familial relationships. These results suggest that Ae. aegypti...

Aedes aegypti é considerado o principal vetor de arboviroses que acomentem os seres humanos. Até o momento a única medida disponível para erradicação da dengue, é o controle do vetor, Ae. aegypti. O conhecimento aprofundado sobre a estruturação genética e dinâmica populacional dessa espécie em diferentes ambientes é crucial, uma vez que populações geneticamente diferentes podem apresentar diferenças quanto à capacidade e competência vetorial. O Brasil possui regiões com diferentes características climáticas e geográficas, assim o conhecimento detalhado sobre populações de mosquitos que colonizam diferentes habitats, é pertinente. Este trabalho avaliou a estrutura populacional de mosquitos Ae. aegypti provenientes de cinco cidades do Brasil (i.e., Belo Horizonte, Botucatu, Campo Grande, Maringá e Rondonópolis) utilizando marcadores microssatélites. Ainda, empregouse esses marcadores para investigar a dinâmica de oviposição e consequente dispersão de mosquitos Ae. aegypti em Botucatu. Em macro-análises populacionais, utilizando DAPC, observamos agrupamento entre indivíduos de mesma localidade e estruturação populacional para mosquitos de Belo Horizonte. Análises de micro-estruturação populacional identificaram seis sub-populações de mosquitos Ae. aegypti entre as seis sub-regiões de Belo Horizonte, ainda foram sugeridas estruturação populacional intermediária para mosquitos das sub-regiões de Campo Grande e falta de estruturação genética entre mosquitos das subregiões de Botucatu. Com esses resultados acreditamos que estruturação genética ocorra em correlação com o tamanho da cidade - localidades maiores parecem proporcionar estruturação genética para populações de mosquitos Ae. aegypti. Análises de PCA em ovitrampas da cidade de Botucatu apontaram organização populacional de Ae. aegypti em famílias. Análises de Pedigree e coeficiente de inbreeding, indicaram que de 30 mosquitos...
Keywords: Aedes aegypti - Genética; Arboviroses; Dengue; Vetores artropodes; Inseto - População; Aedes aegypti; Insect populations